Tinjauan Desain Website Kemlu.Go.Id - Widhyatmoko, Danu (Humaniora, 2013)
Review of kemlu.go.id website design is a research report on Kemlu.go.id website design. Kemlu.go.id website aims to be the information gateway of Ministry of Foreign Affairs, and also as guidelines of foreign politic policies of Republic of Indonesia. The review had been accomplished by using analytical method based on the "Nine Essential Principles for Good Web Design" developed by Collis Ta'eed (2007). At the end of the article, several recommendations in developing kemlu.go.id website are presented to create better appearance.